Academic Procrastination among College Students : Causal Factors and Means of Prevention - Pyong Ho Kim (International Journal of Advanced Culture Technology(IJACT), 2025)
Academic procrastination is a common phenomenon among college students where individuals knowingly delay their assignments, expecting negative consequences. The present study, mainly consisting of literature review, examined the complex nature of procrastination, focusing on the causes, outcomes, and components suggested for relevant interventions. Research suggests the following features as the causal factors of college students’ procrastination: fear for failure, low selfefficacy, and perceived irrelevance in the given tasks. Negative consequences of procrastination include higher anxiety and depression, damaged academic performance, and impaired mental health. Though a few studies indicated potential benefits of procrastination, its overall impact is highly detrimental. Interventions aiming to reduce procrastination are suggested to consist of a few components, including certain cognitive-behavioral strategies, addressing emotional approaches, and creating socially supportive environments. The literature review methodology applied to the present study contains certain limitations, such as heavy reliance on existing research, potentially restraining novel viewpoints, and inclusion of various perspectives of stakeholders. Future researchers interested in this theme are encouraged to further explore the long-term effects of procrastination, the interplay between procrastination and mental health, and to develop interventions that are culturally sensitive. The present study discusses the need for an extensive comprehension for college students’ academic procrastination in order to generate effective interventions that promote their academic success as well as well-being.